The Effect of Capital Gains Taxes on Business Creation and Employment: The Case of Opportunity Zones - Arefeva, Alina; Davis, Morris A.; Ghent, Andra C.; Park, Minseon (Management Science, 2025)
The Tax Cuts and Jobs Act of 2017 established a new program called Opportunity Zones (OZs) that reduces or eliminates capital gains taxes on investment in a limited number of low-income Census tracts. We provide a model illustrating how a change in capital taxation affects employment in existing and new establishments. We then use establishment-level data to show that, in its first two years, the OZ designation increased employment growth relative to comparable tracts by between 3.0 and 4.5 percentage points in metropolitan areas. The job growth occurred in multiple industries and persisted into 2021 rather than quickly disappearing. However, most of the jobs created by the program were likely taken by residents who live outside of the designated tracts, consistent with only 5% of U.S. residents working in the same Census tract as the one in which they live. This paper was accepted by Tomasz Piskorski, finance. Funding: The authors are grateful for the financial support of an award from UW-Madison’s Fall Research Competition. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.03223 .